Torsional behaviour of reinforced concrete beam wrapped with aramid fiber - Sachin B. Kandekar; Rajshekhar S. Talikoti (Journal of King Saud University: Engineering Sciences, 2019)
Present study gives the torsional behaviour of Reinforced Concrete (RC) beam of M30 grade of concrete strengthened with aramid fiber. The aramid fiber as an externally bonded reinforcement used for increasing flexural strength, an attempt is made to use it for improving torsional behaviour of RC beam. Torsional failure mostly occurs in seismic affected areas subjected to sudden failure. Torsional failure is brittle type failure occurs due to undesirable loading.RC beam strengthened with aramid fiber tested for torsional moment using lever arms subjected to equal static loading which transfer equal torsional moment to the beam. The cross section of beam is 150 mm × 300 mm and of 1 m in length. In that three beams were designed for torsional reinforcement and nine as conventional beams. Beam is designed for torsion as per IS456-2000. Building designed earlier using the codes were insufficient to cater for torsional reinforcement. This research investigates behaviour of such conventional beams for torsion when wrapped with aramid fiber. Torsional moments of such strengthened beams are compared with torsionally designed beams which are designed as per new design codes. The study is restricted to aramid fiber fully wrapped and wrapped in strips at width 100 mm of U shape on three faces of beam by using epoxy resin.Experimental result includes ultimate loads & first cracking loads, angle of twist and twisted shape of the beam. Result shows that fully wrapped RC beam gives more torsional strength as compared to controlled beam and there is significant improvement in torsional strength of beams wrapped in strips. After first crack, beam shows tendency to carry load with increase in angle of twist. Thus it is easy method for strengthening of RC beams. Keywords: Torsional behaviour, Reinforced concrete, Lever arms, Aramid fiber, Epoxy resin, Angle of twist